Causes of Disputes in Construction: A Fuzzy Synthetic Evaluation - Yasir Alhammadi; Afiqah R. Radzi; Rahimi A. Rahman (Journal of Engineering, Project, and Production Management)
Construction project disputes are a prevalent issue and require prompt resolution to prevent project delays. Efficient dispute resolution is critical for the success of construction projects. Therefore, the aim of this study is to identify the critical causes of disputes in the Malaysian construction industry and assess their underlying causes. A survey was developed to collect data on the causes of disputes and distributed among industry professionals. The data collected from 125 respondents was analyzed using normalized mean analysis, factor analysis, and fuzzy synthetic evaluation (FSE). Four critical causes of disputes were identified: poorly managed construction processes leading to resource shortages and quality issues, improper contract administration, non-compliance with contractual obligations by either party and errors or omissions in contract documents. Factor analysis revealed that these causes could be categorized into two main components: stakeholder challenges and contractual issues. The FSE results indicated that the components ranged from slightly critical to moderately critical. The study contributes to the literature by categorizing the causes of disputes into stakeholder challenges and contractual issues, offering a structured framework for addressing disputes. The study also highlights the need for improved stakeholder collaboration and contract management to mitigate disputes effectively.